A national center for persistent severe pain after groin hernia repair: Five-year prospective data. Issue 33 (August 2019) - Jensen, Elisabeth Kjær; Ringsted, Thomas K.; Bischoff, Joakim M.; Petersen, Morten A.; Rosenberg, Jacob; Kehlet, Henrik; Werner, Mads U.
Abstract : Abstract: Severe persistent pain after groin hernia repair impairs quality-of-life. Prospective, consecutive cohort study including patients with pain-related impairment of physical and social life. Relevant surgical records were obtained, and examinations were by standardized clinical and neurophysiological tests. Patients demonstrating pain sensitivity to pressure algometry in the operated groin underwent re-surgery, while patients with neuropathic pain received pharmacotherapy. Questionnaires at baseline (Q0) and at the 5-year time point (Q5Y) were used in outcome analyses of pain intensity (numeric rating scale [NRS] 0–10) and pain-related effect on the activity-of-daily-living (Activities Assessment Scale [AAS]). Data are mean (95% CI). Analyses were made in 172/204 (84%) eligible patients. In 54/172 (31%) patients re-surgery (meshectomy/selective neurectomy) was performed, while the remaining 118/172 (69%) patients received pharmacotherapy. In the re-surgery group, activity-related, and average NRS-scores at Q0 were 6.6 (5.6–7.9) and 5.9 (5.6–5.9), respectively. Correspondingly, NRS-scores at Q5Y was 4.1 (3.3–5.1) and 3.1 (2.3–4.0; Q0 vs. Q5Y: P < .0005), respectively. Although both groups experienced a significant improvement in AAS-scores comparing Q0 vs. Q5Y (re-surgery group: 28% (4–43%; P < .0001); pharmacotherapy group: 5% (0–11%; P = .005)) the improvement was significantly larger in the re-surgery group ( P = .02). This 5-year cohort study in patients with severe persistent pain after groin hernia repair signals that selection to re-surgery or pharmacotherapy, based on examination of pain sensitivity, is associated with significant improvement in outcome. Analyzing composite endpoints, combining pain and physical function, are novel in exploring interventional effects. ClinicalTrials.gov Identifier NCT03713047 Abstract : Supplemental Digital Content is available in the text